Effect of HIF‐1α/miR‐10b‐5p/PTEN on Hypoxia‐Induced Cardiomyocyte Apoptosis. Issue 18 (17th September 2019) - Wu, Liping; Chen, Yafen; Chen, Yuanyuan; Yang, Wenbo; Han, Yanxin; Lu, Lin; Yang, Ke; Cao, Jiumei
Abstract : Background: Few reports have addressed the mechanism by which microRNA miR‐10b‐5p regulates post–myocardial infarction (post‐MI) cardiomyocyte apoptosis under hypoxic conditions. Methods and Results: C57BL/6 mice underwent surgical ligation of the left anterior descending artery to create an MI or ischemia/reperfusion animal model. The expression of miR‐10b‐5p, PTEN (phosphatase and tensin homolog), and HIF‐1α (hypoxia‐inducible factor 1α) was detected in infarct border zone tissues at various time points. After precordial injections of the negative control or miR‐10b‐5p, overexpression lentiviruses were made in the areas surrounding the MI sites at 1 week, and myocardial infarct size, cardiac function, and cardiomyocyte apoptosis were examined. A miR‐10b‐5p mimic was transfected into primary mouse cardiomyocytes to analyze its effects on cardiomyocyte apoptosis and PTEN expression. Meanwhile, PTEN as a target of miR‐10b‐5p was verified via luciferase reporter gene assays. Cotransfection of miR‐10b‐5 and PTEN verified the relationship between miR‐10b‐5 and PTEN. Under hypoxic stress, the expression of HIF‐1α and miR‐10b‐5p was examined. The results showed that miR‐10b‐5p expression was markedly reduced in the infarct border zone. Overexpression of miR‐10b‐5p in the murine model of MI significantly reduced MI size, improved cardiac function, and inhibited apoptosis. Overexpression of miR‐10b‐5p in vitro antagonized hypoxia‐induced cardiomyocyte apoptosis and specifically inhibited the expression of the apoptosis‐related gene PTEN, but overexpression of PTEN weakened these effects. We also found that hypoxia‐induced accumulation of HIF‐1α resulted in decreased expression of miR‐10b‐5p. Interfering with the activation of the HIF‐1α signaling pathway promoted Pri‐miR‐10b and miR‐10b‐5p expression and inhibited PTEN expression. Conclusions: MicroRNA miR‐10b‐5p antagonizes hypoxia‐induced cardiomyocyte apoptosis, indicating that miR‐10b‐5p may serve as a potential future clinical target for the treatment of MI.